2010
DOI: 10.1093/brain/awq180
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model for eukaryotic translation initiation factor 2B-leucodystrophy reveals abnormal development of brain white matter

Abstract: Eukaryotic translation initiation factor 2B is a major housekeeping complex that governs the rate of global protein synthesis under normal and stress conditions. Mutations in any of its five subunits lead to leucoencephalopathy with vanishing white matter, an inherited chronic-progressive fatal brain disease with unknown aetiology, which is among the most prevalent childhood white matter disorders. We generated the first animal model for the disease by introducing a point mutation into the mouse Eif2b5 gene lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
88
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(96 citation statements)
references
References 44 publications
6
88
0
Order By: Relevance
“…VWM mice have a higher proportion of small-caliber axons than do WT animals (present study; ref. 30). Scattered axonal swellings are only detected in the oldest mutants with advanced disease, but the axonal cytoskeleton appears otherwise intact.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VWM mice have a higher proportion of small-caliber axons than do WT animals (present study; ref. 30). Scattered axonal swellings are only detected in the oldest mutants with advanced disease, but the axonal cytoskeleton appears otherwise intact.…”
Section: Discussionmentioning
confidence: 99%
“…Additional manipulations may force mice to develop a phenotype that more closely matches that of the human disease, but these have the unwanted side effect of influencing the disease mechanisms (49-52). Geva et al (30) previously generated a VWM mouse model by inserting Arg132His into eIF2Bε, a mutation that in the homozygous state in humans is associated with childhood-onset disease and death in adolescence. This mutant mouse had a normal lifespan, subtle motor impairment at most, and white matter abnormalities that only became manifest after experimental demyelination (30,53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, our results indicate that axons and relative myelin sheath thickness are initially normal or close to normal and only secondarily axonal atrophy occurs, dependent on disease severity. Previously, a different Eif2b5 mutant mouse model was reported to display a higher proportion of thin axons in the internal capsule associated with thinner myelin sheaths and a normal G‐ratio at 3 weeks 33. Axonal diameter and myelin sheath thickness at later ages were not reported, but it was demonstrated that in the cerebral peduncle of 15‐month‐old mutants an increased proportion of axons had no or thinner myelin than of wild‐type mice.…”
Section: Discussionmentioning
confidence: 99%
“…Oligodendrocyte dysfunction and myelin abnormalities are found in a wide variety of neurological diseases and may be involved in the pathophysiology of various diseases, including genetic leukodystrophies [74], schizophrenia and bipolar disorder [75,76], brain injury [77], and endocrine and metabolic abnormalities [78,79] and neurodegenerative conditions such as strokes [80,81], Parkinson's disease [82], Alzheimer's disease [83][84][85], multiple sclerosis [86], and diabetic encephalopathy [87].…”
Section: Oligodendrocytesmentioning
confidence: 99%